Răspuns :
Explicație pas cu pas:
41.a)
[tex](1 + 2 + 3 + ... + 36) \div ( - 18) = \frac{36 \times 37}{2 \times ( - 18)} \\ = \frac{36 \times 37}{ - 36} = - 37[/tex]
b)
[tex]( - 1 - 2 - 3 - ... - 25) \div ( - 26) = \\ = - (1 + 2 + 3 + ... + 25) \div ( - 26) \\ = \frac{25 \times 26}{2 \times 26} = \frac{25}{2}[/tex]
42.
[tex]\{\left[{( - 6)}^{2} + {2}^{3}\right]\times ( - 4) - \left[( - 6) + {( - 3)}^{2} \right]\} \div ( - 11) = \\[/tex]
[tex]= \left[(36 + 8) \times ( - 4) - ( - 6 - 27) \right] \div ( - 11) \\[/tex]
[tex]= \left[44 \times ( - 4) - ( - 33) \right] \div ( - 11) \\[/tex]
[tex]= ( - 176 + 33) \div ( - 11)[/tex]
[tex]= ( - 143) \div ( - 11) = 13[/tex]
43.
[tex]36 \div \{\left[{( - 3)}^{3} + 2\right] \div ( - 5) + \left[( - 18) \div {( - 3)}^{2} \right]\} = \\[/tex]
[tex]= 36 \div \left[( - 27 + 2) \div ( - 5) + ( - 18 \div 9) \right] \\[/tex]
[tex]= 36 \div \left[( - 25) \div ( - 5) + ( - 2) \right] \\[/tex]
[tex]= 36 \div (5 - 2) = 36 \div 3 = 12[/tex]
44.a)
[tex]{( - 1)}^{1} \cdot {( - 1)}^{2} \cdot {( - 1)}^{3} \cdot\cdot...\cdot {( - 1)}^{20} = \\[/tex]
[tex]= {( - 1)}^{1 + 2 + 3 + ... + 20} = {( - 1)}^{210} = 1 \\ [/tex]
b)
[tex]{( - 1)}^{1} + {( - 1)}^{2} + {( - 1)}^{3} + ... + {( - 1)}^{20} = \\ [/tex]
[tex] = ( - 1) + 1 + ( - 1) + 1 + ... + ( - 1) + 1 \\ [/tex]
[tex]= ( - 1 + 1) + ( - 1 + 1) + ... + ( - 1 + 1) \\ [/tex]
[tex]= 0 + 0 + ... + 0 = 0[/tex]